2019
DOI: 10.1021/acs.jmedchem.9b00147
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Peptidomimetics as Selective Inhibitors for the β-Catenin/T-Cell Factor Protein–Protein Interaction

Abstract: The β-catenin/T-cell factor (Tcf) protein–protein interaction (PPI) plays a critical role in the β-catenin signaling pathway which is hyperactivated in many cancers and fibroses. Based on compound 1, which was designed to target the Tcf4 G13ANDE17 binding site of β-catenin, extensive structure–activity relationship studies have been conducted. As a result, compounds 53 and 57 were found to disrupt the β-catenin/Tcf PPI with the Ki values of 0.64 and 0.44 μM, respectively, and exhibit good selectivity for β-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…β-catenin is an important intracellular signal molecule in wnt/β-catenin pathway (Valenta et al, 2012). Up-regulation of β-catenin can combine with T lymphokines or transcription factors of lymphoenhancer family (TCF/LEF) to activate the expression of Wnt pathway target genes, including bone morphogenetic protein (BMP) 2 and 4, CD44, MMP-7 and MMP-13, interleukin-8 and so on (Doumpas et al, 2019;Wang et al, 2019b). The activation of wnt/β-catenin played a positive role in the progression of IVDD (Kondo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin is an important intracellular signal molecule in wnt/β-catenin pathway (Valenta et al, 2012). Up-regulation of β-catenin can combine with T lymphokines or transcription factors of lymphoenhancer family (TCF/LEF) to activate the expression of Wnt pathway target genes, including bone morphogenetic protein (BMP) 2 and 4, CD44, MMP-7 and MMP-13, interleukin-8 and so on (Doumpas et al, 2019;Wang et al, 2019b). The activation of wnt/β-catenin played a positive role in the progression of IVDD (Kondo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…TCF transcription factors recognize the armadillo repeat domain of β‐catenin via an elongated peptide sequence (green, Figure 1 a) with two central hot spot residues crucially contributing to binding. Previous structure‐based efforts to generate ligands targeting the corresponding site on β‐catenin (binding site 3) [20e, 30] have not resulted in therapeutically useful inhibitors. Herein, we took a novel approach towards the generation of ligands for β‐catenin's binding site 3 using E‐cadherin as a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…UU‐T02 exhibits low cell‐based activity probably due to its poor cell membrane permeability which is caused by its two carboxylate groups. Further optimization of UU‐T02 was performed to increase its activities in both biochemical and cell‐based studies 112 . Extensive SAR studies not only demonstrate that the naphthyl group, two carboxylate groups, and the 5‐Cl indole moiety are critical for maintaining the inhibitory activity, but also reveal that the methyl ester of UU‐T02 can be replaced by the larger hydrophobic groups, and the carboxylate groups can be substituted by its bioisosteres to improve activity.…”
Section: Inhibitors Of the β‐Catenin/tcf Ppimentioning
confidence: 99%
“…Extensive SAR studies not only demonstrate that the naphthyl group, two carboxylate groups, and the 5‐Cl indole moiety are critical for maintaining the inhibitory activity, but also reveal that the methyl ester of UU‐T02 can be replaced by the larger hydrophobic groups, and the carboxylate groups can be substituted by its bioisosteres to improve activity. These efforts have led to new inhibitors with improved activity ( K i = 0.44 μ M) 112 . Cell‐based studies showed that the last inhibitor in Figure 4 selectively disrupted β ‐catenin/TCF over β ‐catenin/E‐cadherin and β ‐catenin/APC interactions, dose‐dependently suppressed transactivation of Wnt/ β ‐catenin signaling, inhibited growth of Wnt/ β ‐catenin signaling‐hyperactive cancer cells, and blocked migration and invasiveness of Wnt/ β ‐catenin‐dependent cancer cells.…”
Section: Inhibitors Of the β‐Catenin/tcf Ppimentioning
confidence: 99%